ABA Inhibits Rice Seed Aging by Reducing H2O2 Accumulation in the Radicle of Seeds - Qin Zheng; Zhenning Teng; Jianhua Zhang; Nenghui Ye (Plants, 2024)
The seed, a critical organ in higher plants, serves as a primary determinant of agricultural productivity, with its quality directly influencing crop yield. Improper storage conditions can diminish seed vigor, adversely affecting seed germination and seedling establishment. Therefore, understanding the seed-aging process and exploring strategies to enhance seed-aging resistance are paramount. In this study, we observed that seed aging during storage leads to a decline in seed vigor and can coincide with the accumulation of hydrogen peroxide (H2O2) in the radicle, resulting in compromised or uneven germination and asynchronous seedling emergence. We identified the abscisic acid (ABA) catabolism gene, abscisic acid 8′-hydroxylase 2 (OsABA8ox2), as significantly induced by aging treatment. Interestingly, transgenic seeds overexpressing OsABA8ox2 exhibited reduced seed vigor, while gene knockout enhanced seed vigor, suggesting its role as a negative regulator. Similarly, seeds pretreated with ABA or diphenyleneiodonium chloride (DPI, an H2O2 inhibitor) showed increased resistance to aging, with more robust early seedling establishment. Both OsABA8ox2 mutant seeds and seeds pretreated with ABA or DPI displayed lower H2O2 content during aging treatment. Overall, our findings indicate that ABA mitigates rice seed aging by reducing H2O2 accumulation in the radicle. This study offers valuable germplasm resources and presents a novel approach to enhancing seed resistance against aging.